First Biologic Drug in the Treatment of RAS Wild-Type Metastatic Colorectal Cancer: Anti-EGFR or Bevacizumab? Results From a Meta-Analysis - Ottaiano, Alessandro (Front Pharmacol, 2018)
Introduction: We performed a meta-analysis in order to analyze and quantify the effect on survival of starting therapy in RAS wild-type (wt) metastatic colorectal cancer (mCRC) patients with anti-EGFR agents or bevacizumab. Patients and Methods: Randomized, phase II or III, clinical trials reporting overall survival (OS) in RAS wt mCRC patients treated with first-line chemotherapy (CT) associated with bevacizumab or anti-EGFR agents were selected. The primary end-point of this meta-analysis was OS; findings were depicted in classical Forest plots. Results: Seven studies met the criteria for meta-analysis including 3,805 patients. The pooled second-line cross-over rate to bevacizumab was 36.6%, to anti-EGFR 33.2%. Only one study was selected reporting comparison between CT vs. CT plus bevacizumab in RAS wt patients with a HR of 1.13 in favor of CT (CI: 0.89–1.43, p = 0.317). The pooled HRs were 0.89 (95% CI: 0.79–1.00) for CT plus anti-EGFR vs. CT and 0.81 (95% CI: 0.71–0.92) in favor of CT plus anti-EGFR vs. CT plus bevacizumab. Subgroup analysis showed a positive prognostic impact of starting CT plus anti-EGFR in left colon cancer (pooled HR: 0.70; CI: 0.54–0.85) while a positive trend of starting CT plus bevacizumab was observed in right colon cancer (pooled HR: 1.29; CI: 0.81–1.77). Conclusions: This meta-analysis shows that starting therapy in RAS wt mCRC patients with an anti-EGFR agent improves OS when the primary tumor location is in the left colon but a strong limitation of previous studies is the very low rate of biologic drug therapy cross-over.